Earning Management: The Role of Corporate Governance, Reputation and Financial Distress - Suhaemi, Ujang; Hidayah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study is motivated by the importance of implementing Good Corporate Governance (GCG) and maintaining a strong corporate reputation in managing earnings, particularly when companies are experiencing financial distress. The primary objective of this research is to examine the effects of GCG and corporate reputation on earnings management, as well as to investigate the moderating role of financial distress in these relationships. A quantitative approach was employed using panel data, with a sample consisting of 28 consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The data analysis technique used was panel data regression with moderation testing. The results indicate that both GCG and corporate reputation have a significant effect on earnings management, with significance levels below 5%. Moreover, financial distress was found to weaken the influence of GCG on earnings management, while strengthening the impact of corporate reputation on earnings management practices. These findings suggest that a company's financial condition plays a crucial role in determining the effectiveness of GCG and corporate reputation in influencing earnings management behavior. The conclusion of this study highlights the critical importance of adhering to sound governance principles and cultivating a strong corporate reputation, especially when facing financial pressure.